National Landscape of Human Immunodeficiency Virus–Positive Deceased Organ Donors in the United States. (28th August 2021) - Werbel, William A; Brown, Diane M; Kusemiju, Oyinkansola T; Doby, Brianna L; Seaman, Shanti M; Redd, Andrew D; Eby, Yolanda; Fernandez, Reinaldo E; Desai, Niraj M; Miller, Jernelle; Bismut, Gilad A; Kirby, Charles S; et al.
Abstract: Background: Organ transplantation from donors with human immunodeficiency virus (HIV) to recipients with HIV (HIV D + /R + ) presents risks of donor-derived infections. Understanding clinical, immunologic, and virologic characteristics of HIV-positive donors is critical for safety. Methods: We performed a prospective study of donors with HIV-positive and HIV false-positive (FP) test results within the HIV Organ Policy Equity (HOPE) Act in Action studies of HIV D + /R + transplantation (ClinicalTrials.gov NCT02602262, NCT03500315, and NCT03734393). We compared clinical characteristics in HIV-positive versus FP donors. We measured CD4 T cells, HIV viral load (VL), drug resistance mutations (DRMs), coreceptor tropism, and serum antiretroviral therapy (ART) detection, using mass spectrometry in HIV-positive donors. Results: Between March 2016 and March 2020, 92 donors (58 HIV positive, 34 FP), representing 98.9% of all US HOPE donors during this period, donated 177 organs (131 kidneys and 46 livers). Each year the number of donors increased. The prevalence of hepatitis B (16% vs 0%), syphilis (16% vs 0%), and cytomegalovirus (CMV; 91% vs 58%) was higher in HIV-positive versus FP donors; the prevalences of hepatitis C viremia were similar (2% vs 6%). Most HIV-positive donors (71%) had a known HIV diagnosis, of whom 90% were prescribed ART and 68% had a VL <400 copies/mL. The median CD4 T-cell count (interquartile range) was 194/µL (77–331/µL), and the median CD4 T-cell percentage was 27.0% (16.8%–36.1%). Major HIV DRMs were detected in 42%, including nonnucleoside reverse-transcriptase inhibitors (33%), integrase strand transfer inhibitors (4%), and multiclass (13%). Serum ART was detected in 46% and matched ART by history. Conclusion: The use of HIV-positive donor organs is increasing. HIV DRMs are common, yet resistance that would compromise integrase strand transfer inhibitor–based regimens is rare, which is reassuring regarding safety. Abstract : Under the HOPE Act, 92 donors (58 human immunodeficiency virus [HIV] positive, 34 false-positive) donated 177 organs to recipients with HIV. Many donors (64%) were taking antiretrovirals, and although HIV drug resistance was common (42%), multiclass (12%) and integrase strand transfer inhibitor resistance (4%) was rare.